Safety practices, perceived risk, risk coping, stigma and anxiety: experience in dealing with covid-19 pandemic infectious disease among frontline healthcare workers in Hospital Universiti Sains Malaysia - Nor, Nor Iryani Mahd (2023)
The COVID-19 pandemic has affected more than 114 countries, including Malaysia. By October 2022, Malaysia had recorded a total of 4.8 million COVID-19 cases with a death toll of 36 thousand. As frontliners in the battle against the ongoing pandemic, healthcare workers (HCWs) have experienced a significant burden from COVID-19, as they are directly involved in screening and treating patients. The aims of this study were to examine the proportion of safety practices, perceived risk, stigma, as well as anxiety levels and its associated factors among the HCWs of Hospital Universiti Sains Malaysia (USM) during the late stage of the COVID-19 pandemic. A cross-sectional study involving an online survey of 252 HCWs was conducted from September 2021 to March 2022. The data were analysed using simple and multiple linear regression. The results showed mean (standard deviation (SD)) scores of 63.54 (5.78) for HCWs’ safety practices, 10.06 (1.62) for organizational safety practices, 11.65 (2.90) for perceived risk, and 10.45 (4.74) for stigma. The prevalence of positive anxiety, defined as a GAD-7 score of ≥ 8, was 14 (5.6%). Ethnicity, safety practices, perceived risk, maladaptive and distancing coping strategies, and stigma were significant associated factors of anxiety levels. Our study highlighted that HCWs at Hospital USM had practised appropriate safety measures, experienced substantial perceived risk and stigma, while maintaining a low level of anxiety during the late stage of the COVID-19 pandemic. We recommend the implementation of good standard operating procedures, provision of adequate protective equipment, and strong mental health support in combatting infectious disease pandemics.